(3QhVI GdWGdHjf hYeOI GdeJbjfs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3GdQGaYj , CHh GdbGSe YHO GdcQje Hf eMeO Hf YHO GdcQje GdQGaYj GdbRhjfj, GdQGaYj GdbRhjfj,J (B623 (3g` s
(3ChdgG (B:s
(3CeG HYO aGdGTJZGd HGdYde ef CaVd GdbQH hCLd GdWGYGJ hCge CfhGY GdNjQ s
(3BNQgG (B:s
(3hdhhba TjFkG djTJQi ef ZdJg RjJkG Ch ZjQg djSHM ai eSLOkG hZjQg aMceg ai GdUMI eG PcQfGg ai GdfPQ hGddg CYde BNQ GdeLdO GdChd ef GdQhVI s
(3fSNI KGefIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs